Exercise related ventilation dynamics and clinical correlates in patients with fibrotic idiopathic interstitial pneumonias - De Martino, Marina; Cobuccio, Raffaele; Bruzzese, Dario; Rea, Gaetano; Meoli, Ilernando; Stefanelli, Francesco; Canora, Angelo; Capaccio, Annalisa; Sanduzzi, Alessandro; Matarese, Alessandro; Bocchino, Marialuisa (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Assessment of exercise performance is a key component in the management of interstitial lung diseases, as its limitation may occur very early. Aim of the present study was to assess ventilation dynamics in combination with pulse-oximetry changes in 54 clinically stable patients affected by idiopathic pulmonary fibrosis or idiopathic fibrotic nonspecific interstitial pneumonia. Testing was successfully performed with the Spiropalm 6-MWT Hand-held spirometer by the majority of cases (94%). End test oxygen saturation (SpO2) values